Papua New Guinea Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (Washington, DC, 2015)
The main purpose of the Report on the Observance of Standards and Codes, Accounting and Auditing (ROSC A&A) review exercise, conducted at the request of the Government of Papua New Guinea, is to propose policy recommendations that will strengthen the institutional framework that underpins accounting and auditing practices in the country. Implementation of the policy recommendations will enhance the quality of financial reporting for corporations a key pillar that directly contributes to enhancing the business environment and the advancement of governance and financial accountability in both private and public sector entities. The ROSC A&A review for Papua New Guinea focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting, and involves both a review of mandatory requirements and actual practices. The international standards that have been used as reference points for the preparation of this report are International Financial Reporting Standards (IFRS), clarified International Standards on Auditing (ISA), and international good practice in the field of accounting and auditing regulation. It is critical at this stage of development that PNG manage its resources well. The PNGLNG project shipped its first cargo in June 2014 and it is expected the LNG project to expand GDP by as much as one-quarter in 2014 and 2015, and national income by about 8 per cent. This requires significantly stepping up the quality, compliance, and enforcement of benchmark financial reporting and auditing practices. This is a key development challenge for PNG to channel this windfall revenue into investments that positively impact peoples lives.